2015
DOI: 10.3402/edui.v6.28421
|View full text |Cite
|
Sign up to set email alerts
|

European education policy initiatives and teacher education curriculum reforms in Greece

Abstract: The paper explores the ways in which university-based Teacher Education Departments in Greece have operated to promote changes to their undergraduate curricula. Our research approach views these changes as responses to the policies of the European Union and the Bologna Process for the 'modernisation' of higher education systems across Europe. Data are drawn from qualitative analyses of 18 curricula in two periods of their development, the middle of the 1990s and the late 2000s. The analysis of the study is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…One of the contributions of this study is that the overarching regulative discourse operative in the primary teacher education programmewhat it is guiding future teachers towardsis in line with results of previous studies done on education policy in Sweden (Beach andBagley 2012, 2013;Sjöberg 2011), and in the European perspective as well (Garm and Karlsen 2004;Cochran Smith 2005;Zeichner 2010Zeichner , 2012Wågsås Afdal 2012, 2013, 2016Sarakinioti and Tsatsaroni 2015). This shows the substantial influence global policy discourses have on educational practiceswhat they should look like and how they should be carried outand the way these discourses shape both policy and practice, nationally and internationally.…”
Section: Discourses a Related Question Was How The Assessment Practisupporting
confidence: 81%
See 2 more Smart Citations
“…One of the contributions of this study is that the overarching regulative discourse operative in the primary teacher education programmewhat it is guiding future teachers towardsis in line with results of previous studies done on education policy in Sweden (Beach andBagley 2012, 2013;Sjöberg 2011), and in the European perspective as well (Garm and Karlsen 2004;Cochran Smith 2005;Zeichner 2010Zeichner , 2012Wågsås Afdal 2012, 2013, 2016Sarakinioti and Tsatsaroni 2015). This shows the substantial influence global policy discourses have on educational practiceswhat they should look like and how they should be carried outand the way these discourses shape both policy and practice, nationally and internationally.…”
Section: Discourses a Related Question Was How The Assessment Practisupporting
confidence: 81%
“…Teacher education and the shaping of professional knowledge base and identity Finally, several research projects have shown that both teacher education policy and the content of a teacher education programme affects both the knowledge base and the teacher's professional identity (Beck and Young 2005;Tatto 2006;Sarakinioti and Tsatsaroni 2015). For example, Wågsås Afdal (2012,2013,2016) and Wågsås Afdal and Nerland (2014) show that various traditions affect not only content but also which knowledge base and teacher identity is created through the programme.…”
Section: The Swedish Teacher Education In a European Policy Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This is true not only for Sweden but for the rest of the world (Antikainen, 2010;Briant & Doherty, 2012;Cochran-Smith & Fries, 2001;Goodson, 2008;Lauder, Brown, & Halsey, 2009;Lawn & Furlong, 2009;Sarakinioti & Tsatsaroni, 2015) and is in line with the discourse of knowledge-based societies and economies (Apple, 2001;Ball, 2008;Garm & Karlsen, 2004;Young, 2009). The reform of teacher education can also be seen as part of the overarching education reform in Sweden that was made around 2010 and with the political purpose of improving the results in Swedish schools.…”
Section: Swedish Teacher Education In a Historical And Discursive Conmentioning
confidence: 87%
“…Orientation is defined in terms of ‘introverted’ or ‘extroverted’ meanings, corresponding to introjected or projected types of identity formation. The former promotes inwardness, generating inner commitments related to the perceived intrinsic value of specific knowledge domains, while the latter promotes outwardness reflecting demands and contingencies of external fields of practice (Beck and Young, 2005; Bernstein, 2000; Sarakinioti, 2012; Sarakinioti et al, 2011).…”
Section: ‘Modernising’ Greek Educational Administration: An Illustratmentioning
confidence: 99%